Absence of systemic toxicity changes following intramuscular administration of novel pSG2.HIVconsv DNA, ChAdV63.HIVconsv and MVA.HIVconsv vaccines to BALB/c mice. - Ondondo, B; Brennan, C; Nicosia, A; Crome, S; Hanke, T (2013)
BACKGROUND: The systemic toxicity of three candidate HIV-1 vaccines plasmid pSG2.HIVconsv DNA (D), ChAdV63.HIVconsv (C) and MVA.HIVconsv (M) expressing chimeric immunogen derived from the most conserved regions of the HIV-1 proteome was evaluated in two repeat-dose studies in the male and female BALB/c mice. METHODS: In study UNO011, mice received three doses of 2×10(7) plaque-forming units of MVA.HIVconsv vaccine (MMM). In study UNO012, mice received 3 doses of 50μg of pSG2.HIVconsv DNA followed by a single dose of 5.95×10(9) virus particles of ChAdV63.HIVconsv vaccine (DDDC). Similarly constituted control groups received the vehicle alone (phosphate buffered saline) at the same volume-dose. All vaccines were administered by intramuscular needle injection into the right hind limb at 14-day intervals and animals were sacrificed 7 days after the last dose. Assessment of local and systemic toxicity was made. Induction of HIV-1-specific responses was confirmed. Parameters assessed included clinical condition, body weight, food consumption, ophthalmoscopy, haematology, blood chemistry, organ weight and macroscopic and microscopic pathology. RESULTS: In both studies, treatment with the candidate vaccines elicited strong HIV-1-specific T-cell responses. The vaccine treatment was well-tolerated without any adverse systemic toxicological changes. The local toxicity findings observed in these studies were consistent with the predicted response to a vaccine/substance administration by intramuscular injection. CONCLUSIONS: The three novel anti-HIV-1 vaccines were well tolerated when administered by intramuscular injection to BALB/c mice. These results supported an application for authorisation by the Medicines and Healthcare Products Regulatory Agency of the UK to test these vaccines for the first time in phase I clinical trials in healthy both uninfected subjects and HIV-1-infected patients stable on antiretroviral treatment.